Reactive Template Synthesis of Polypyrrole Nanotubes for Fabricating Metal/Conducting Polymer Nanocomposites. Issue 6 (23rd January 2013) - Zhang, Jun; Liu, Xianghong; Zhang, Lixue; Cao, Bingqiang; Wu, Shihua
Abstract Unique nanocomposites of polypyrrole/Au and polypyrrole/Pt hybrid nanotubes are synthesized employing polypyrrole (PPy) nanotubes as an advanced support by solution reduction. The conducting polymer PPy nanotubes are fabricated by using pre‐prepared MnO2 nanowires as the reactive templates. MnO2 nanowires induce the 1D polymerization of pyrrole monomers and the simultaneous dissolution of the templates affords the hollow tube‐like structure. The loading content of metal nanoparticles in the nanocomposites could be adjusted by simply changing the amount of metal precursors. This work provides an efficient approach to fabricate an important kind of metal/conducting polymer hybrid nanotubes that are potentially useful for electrocatalyst and sensor materials.